Cryptocurrencies: the present and the future in world monetary system (International relations and international law Journal, 2018)
Article is devoted to innovations of the financial world which are actual today –cryptocurrencies and problems related to their use in a world financial system. The general characteristic is given and the concept of cryptocurrency is revealed, its main differences from traditional currencies are defined. The analysis of advantages and shortcomings of such cryptocurrencies as bitcoin and litecoin is provided. The main problems related to a wide circulation of virtual money, the relation to cryptocurrencies at the governments of the countries of the world are considered. For today there was no consensus concerning their functioning yet: some countries impose restrictive measures and a ban on their use, and others – consider the possibility of creation of own virtual monetary unit. Also the assessment of future of cryptocurrency bitcoin and its further development is given.Key words: money, currency, cryptocurrency, bitcoin, decentralization, virtual money, transaction, bank.